Opening Editorial of the Second issue 2025 (Journal of human and social sciences, 2025)
In an era of accelerating social, political, and intellectual transformations, where questions become more complex than answers become clear, the humanities and social sciences emerge as indispensable fields for understanding humanity within its context. They analyze phenomena not merely as they appear on the surface, but as they are shaped within the depths of history, culture, and social structure. These sciences do not simply describe reality; they strive to deconstruct, critique, and reconstruct it on more conscious and responsible epistemological foundations. This issue of the Journal of Humanities and Social Sciences, published by the Libyan Authority for Scientific Research, comes within this intellectual framework, contributing to enriching rigorous scientific debate and emphasizing the importance of systematic academic research in addressing the issues of Libyan and Arab society, free from preconceived notions and grounded in the tools of scientific analysis and objective critique. Since its inception, the journal has been committed to being a peer-reviewed academic platform that provides a space for researchers to present serious studies, employing diverse methodologies and complementing their disciplines. This commitment stems from the belief that understanding human reality cannot be achieved from a single perspective or through a singular approach, but rather through an open intellectual dialogue between history, sociology, philosophy, linguistics, economics, political science, and other branches of human knowledge. As we present this issue to our readers, we emphasize that the true challenge for the humanities lies not in accumulating texts or reproducing ready-made pronouncements, but in their ability to question established assumptions and contribute to building a critical consciousness that keeps pace with transformations and anticipates the future. A society that does not think scientifically about itself remains captive to reactions, unable to actively shape its own destiny. In conclusion, the journal's editorial board hopes that the research published in this issue will open new horizons for research and dialogue, and that it will be a valuable addition to the Libyan and Arab academic library, representing another step towards establishing a culture of serious scientific research as a fundamental pillar of intellectual and societal development.